2022
DOI: 10.51662/jiae.v2i1.38
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Changes in ACM Performance in PK-XXX Aircraft with Modification of Cleaning Method to Get a Comfortable Temperature

Abstract: Airplanes are a mode of transportation that people are interested in because they have a relatively short travel time and long distances. Therefore, aircraft is a means of transportation with a high level of safety. One level of safety comes from the aircraft's Air Conditioning (AC) system, which functions as a temperature controller for the aircraft during flight and as a pressure protector during flight. Various components make up an aircraft AC system, one of which is the Air Cycle Machine (ACM). Where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The selection in this study uses the AHP method and the hierarchical structure of the process as shown in Figure 8. Comparison between the criteria components is used to choose best developed alternative design using this AHP method [31,32,33,34]. Pairwise comparison matrices were carried out for comparative assessments between one criterion and another, such as efficiency, power produced, production costs, production time and ease of maintenance.…”
Section: Resultsmentioning
confidence: 99%
“…The selection in this study uses the AHP method and the hierarchical structure of the process as shown in Figure 8. Comparison between the criteria components is used to choose best developed alternative design using this AHP method [31,32,33,34]. Pairwise comparison matrices were carried out for comparative assessments between one criterion and another, such as efficiency, power produced, production costs, production time and ease of maintenance.…”
Section: Resultsmentioning
confidence: 99%
“…This condition is caused by the Increment of AOA on the turbine blades, causing a stall in the flow [26] [27]. The stall is a condition where there is no increase in turbine performance when the AOA increases.…”
Section: Resultsmentioning
confidence: 99%
“…For the record, the parameters of the exhaust gas emission threshold in Indonesia are based on the parameters of carbon monoxide (CO) 1.5% and hydrocarbons (HC) 200 ppm. Vehicle emissions can also indicate problems that occur in car engines [28] [29].…”
Section: Methodsmentioning
confidence: 99%